Seismic Hazard for Regional-Scale Sumatra Island Based on Realistic Physical Computation of Seismic Wave Propagation - Irwandi; Zulfakriza; Muzli; Hassan, Hany M.; Makoto Okubo (UIR PRESS, 2025)
Sumatra traversed by active fault zones leads to an earthquake's danger is a severe concern for the government as disaster mitigation efforts. The provision of a precise seismic hazard map attempts to recognize the hazard and the first step to start the disaster mitigation efforts. However, Indonesia's official hazard map has used the Probabilistic Seismic Hazard Analysis (PSHA) method based on general ground motion prediction equations (GMPE). General GMPE calculates strong ground motion, however, it has not been able to conduct a comprehensive study involving the focal mechanism's structural model and seismogenic zones. On the other hand, the Neo-Deterministic Seismic Hazard Assessment (NDSHA) method can integrate available geological, geophysical, seismological, and geotechnical information to calculate strong ground motion and applied in several countries successfully. Sumatra has oblique subduction causing a resultant force that triggers a right-lateral strike-slip fault activity called the GSF (Great Sumatran Fault). The high seismicity and focal mechanism complexity in Sumatra have been a challenge for implementing the method NDSHA. Structural models under the receiver site necessary for the realistic calculation of synthetic seismograms are divided into polygons aligned with the Sumatra coastline's general orientation. Regarding the data availability and resolution, the crust structural model gets from the LITHO1.0 model. The structural model compilation is validated as input for synthetic seismogram computation and verified by field observations of the instrument seismometer and accelerometer. Seismograms observation data from the Pidie Jaya earthquake on 7 December 2016 with a magnitude of M6.5 shows relatively good validity with synthetic seismograms. The success of synthetic seismogram validity makes us confident to apply strong ground motion calculations throughout Sumatra.